Chitosan/collagen blends with inorganic and organic additive—A review. Issue 6 (9th November 2017) - Kaczmarek, B.; Sionkowska, A.
Abstract: This review provides a report on recent studies of composite materials based on a chitosan and collagen mixture due to their biocompatibility and bioactivity. Those natural polymers are most widely used to obtain biomaterials. However, the materials based on chitosan/collagen complexes present poor mechanical parameters, as well as high swelling behavior and enzymatic degradation rate. Such properties are considered problematic for the material clinical application. An increased interest in composite materials has been observed due to their enhanced physicochemical properties. A composite material preparation involves different compounds addition to natural polymers. Herein, the use of organic and inorganic additives has been reported. Moreover, the potential application of composite materials based on chitosan/collagen complexes in the tissue engineering science has been discussed.